Reproductive Health in the Middle East and North Africa : Well-Being for All - Aoyama, Aoyama (Washington, DC: World Bank, 2013)
This reproductive health review of the Middle East and North Africa (MENA) region provides an overview of the issues and establishes a base of knowledge upon which a strategy could be constructed. Despite achievements in the population and health sectors during the last decades, several reproductive health issues remain, while new challenges have emerged. Major reproductive health issues in the region include high maternal mortality, particularly in Yemen, Morocco, Egypt, and Iraq; high fertility and slowing fertility decline; early marriage and high teenage fertility; the increasing prevalence of sexually transmitted infections and HIV/AIDS; and female genital cutting in Egypt and Yemen. There is a correlation between reproductive health issues, a country's level of social development, and the size of gaps within a country; between men and women, urban and rural, rich and poor. Therefore, it is necessary to plan and implement programs targeted to specific issues and underprivileged groups; develop effective and sustainable health systems with high-quality services; raise awareness and change behaviors of both the public and policymakers; and empower women. Strong political commitment is essential to overcoming social and cultural constraints. Possible intervention components and possible roles of the World Bank are suggested.